2017
DOI: 10.1088/1674-1056/26/11/115101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aperture field distribution on the maximum radiated power at atmospheric pressure

Abstract: The air breakdown in the high-power antenna near-field region limits the enhancement of the radiated power. A model coupling the field equivalent principle and the electron number density equation is presented to study the breakdown process in the near-field region of the circular aperture antenna at atmospheric pressure. Simulation results show that, although the electric field in the near-field region is nonuniform, the electron diffusion has small influence on the breakdown process when the initial electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…1) A lot of studies concentrated on the determination of the breakdown threshold for a given pulse duration, gas composition, and pressure. [2][3][4][5][6][7][8][9][10] In recent years, the plasma patterns in the microwave breakdown have been captured by a fast camera. [11][12][13] The experiments of Hidaka et al showed that the regular filamentary arrays form in the air breakdown at 110 GHz and high pressures.…”
Section: Introductionmentioning
confidence: 99%
“…1) A lot of studies concentrated on the determination of the breakdown threshold for a given pulse duration, gas composition, and pressure. [2][3][4][5][6][7][8][9][10] In recent years, the plasma patterns in the microwave breakdown have been captured by a fast camera. [11][12][13] The experiments of Hidaka et al showed that the regular filamentary arrays form in the air breakdown at 110 GHz and high pressures.…”
Section: Introductionmentioning
confidence: 99%